Rectangle A B C D has A B = 6 and B C = 4 . It is depicted in the above figure. You draw E F parallel to B C and 1 unit to its left. Now you draw rectangle G H I J that is similar to rectangle A B C D inscribed in the shorter rectangle A F E D . If the ratio of the area of G H I J to the area of A B C D is q p , where p and q are positive coprime integers, find p + q .
Note: Similar rectangles have the same length to width ratio.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let H G = I J = x and ∠ J I F = ∠ G J E = θ . Then H I = G J = 3 2 x and
⎩ ⎪ ⎨ ⎪ ⎧ A I + I F = A F E J + J F = E F ⟹ 3 2 x sin θ + x cos θ = 5 ⟹ 3 2 x cos θ + x sin θ = 4 ⟹ 2 x sin θ + 3 x cos θ = 1 5 ⟹ 2 x cos θ + 3 x sin θ = 1 2 . . . ( 1 ) . . . ( 2 )
From ( 2 ) ( 1 ) :
2 x cos θ + 3 x sin θ 2 x sin θ + 3 x cos θ 2 cos θ + 3 sin θ 2 sin θ + 3 cos θ 8 sin θ + 1 2 c o s θ 2 cos θ ⟹ tan θ = 1 2 1 5 = 4 5 = 1 0 cos θ + 1 5 sin θ = 7 sin θ = 7 2 ⟹ sin θ = 5 3 2 , cos θ = 5 3 7
From ( 1 ) : 5 3 4 x + 5 3 2 1 x = 1 5 ⟹ 5 3 2 5 x = 1 5 ⟹ x = 5 3 5 3 . Therefore [ A B C D ] [ G H I J ] = 6 2 x 2 = 1 0 0 5 3 and p + q = 5 3 + 1 0 0 = 1 5 3 .
Let ∠ A H I = θ , H I = 2 x , then:
I J = 2 x × 6 ÷ 4 = 3 x 2 x sin θ + 3 x cos θ = 5 ( 1 ) 2 x cos θ + 3 x sin θ = 4 ( 2 ) 3 × ( 1 ) − 2 × ( 2 ) : ⟹ 5 x cos θ = 7 ( 3 ) 3 × ( 2 ) − 2 × ( 1 ) : ⟹ 5 x sin θ = 2 ( 4 ) ( 3 ) 2 + ( 4 ) 2 : ⟹ x 2 = 2 5 5 3 S A B C D S G H I J = 4 × 6 2 x × 3 x = 4 x 2 = 1 0 0 5 3
Since G H I J is similar to A B C D , let I J = H G = 3 k and H I = G J = 2 k . The ratio of the area of G H I J to the area of A B C D is r = 4 ⋅ 6 2 k ⋅ 3 k = 4 1 k 2 .
By angle chasing the four right triangles are similar by AA similarity. Let θ = ∠ J I F = ∠ G J E = ∠ H G D = ∠ A H I , then I F = G D = 3 k cos θ , F J = D H = 3 k sin θ , H A = E J = 2 k cos θ , and A I = E G = 2 k sin θ , so that from A I + I F = A F :
2 k sin θ + 3 k cos θ = 5 . . . ( 1 )
and from D H + H A = D A :
3 k sin θ + 2 k cos θ = 4 . . . ( 2 )
From ( 1 ) 2 + ( 2 ) 2 we obtain 1 3 k 2 + 2 4 k 2 sin θ cos θ = 4 1 , or
sin θ cos θ = 2 4 k 2 1 ( 4 1 − 1 3 k 2 ) . . . ( 3 )
The area of G H I J is the same as the difference between the area of A D E F and the four right triangles, so 4 ⋅ 5 − ( 2 9 k 2 sin θ cos θ + 2 k 2 sin θ cos θ + 2 9 k 2 sin θ cos θ + 2 k 2 sin θ cos θ ) = 2 k ⋅ 3 k , or
2 0 − 1 3 k 2 sin θ cos θ = 6 k 2 . . . ( 4 )
Substituting ( 3 ) into ( 4 ) and simplifying gives k 2 = 2 5 5 3 .
Therefore, the ratio is r = 4 1 k 2 = 1 0 0 5 3 , so p = 5 3 , q = 1 0 0 , and p + q = 1 5 3 .
Problem Loading...
Note Loading...
Set Loading...
Since rectangle G H I J is similar to rectangle A B C D , H I G H = B C A B = 2 3 Simple angle chasing gives, ∠ D G H = ∠ A H I = ∠ F I J = ∠ E J G Combining this with G H = J I and G J = H I , we get the following relations: △ G D H ≅ △ I F J , △ H A I ≅ △ J E G △ G D H ∼ △ I F J ∼ △ H A I ∼ △ J E G Let D H = x ⟹ A H = 4 − x and A I = y ⟹ F I = G D = 5 − y .
Since △ G D H ∼ △ H A I , y x = 4 − x 5 − y = 2 3 ⟹ x = 5 6 , y = 5 4 Using the Pythagorean Theorem , G H 2 = G D 2 + D H 2 = x 2 + ( 5 − y ) 2 = 2 5 4 7 7 The ratio of the area of G H I J to the area of A B C D is, [ A B C D ] [ G H I J ] = ( A B G H ) 2 = 3 6 2 5 4 7 7 = 1 0 0 5 3
Therefore, p = 5 3 , q = 1 0 0 ⟹ p + q = 1 5 3 .